2012
DOI: 10.1016/j.febslet.2012.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat ingestion activates β‐endorphin neurons in the hypothalamus

Abstract: Edited by Laszlo Nagy Keywords:Dietary fat Pro-opiomelanocortin b-Endorphin Opioid a b s t r a c tThe opioid system regulates food choice, consumption, and reinforcement processes, especially for palatable meals such as fatty food. b-Endorphin is known as an endogenous opioid peptide produced in neurons of the hypothalamus. In this study, we found that Intralipid (fat emulsion) ingestion increased c-fos expression in b-endorphin neurons. However, intragastric infusion of Intralipid only slightly increased c-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Moreover, this role is consistent with the fact that POMC neurons and the opioid system are involved in the regulation of energy homeostasis (14)(15)(16)(17). The POMC neuron can be activated by ingestion of fat but cannot be sufficiently activated by intragastric administration of fat (5). It has also been reported that naltrexone administration can reduce sucrose intake even in animals that have been esophagostomized to prevent post-ingestive effects (24).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Moreover, this role is consistent with the fact that POMC neurons and the opioid system are involved in the regulation of energy homeostasis (14)(15)(16)(17). The POMC neuron can be activated by ingestion of fat but cannot be sufficiently activated by intragastric administration of fat (5). It has also been reported that naltrexone administration can reduce sucrose intake even in animals that have been esophagostomized to prevent post-ingestive effects (24).…”
Section: Discussionsupporting
confidence: 76%
“…We recently reported that fat ingestion induces elevations in the endogenous opioid peptide, beta-endorphin, in cerebrospinal fluid (4). Furthermore, we have also demonstrated that fat ingestion can activate pro-opiomelanocortin (POMC) neurons in the hypothalamus, which synthesize beta-endorphin (5). Many reports have suggested that administration of opioid receptor antagonists can attenuate fat preference, an observation that is consistent with our findings (4,(6)(7)(8).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…16−19) However, pro-opiomelanocortin neurons, which release β-endorphin, are more strongly activated after fat ingestion compared to sucrose ingestion. 20) Similarly, the orexigenic or anorexigenic effects of opioid receptor agonists or antagonists are stronger in mice fed a high-fat diet than in those fed a highcarbohydrate diet. 21,22) These reports suggest that the opioid system is highly involved in the ingestion of dietary fat compared to sucrose.…”
Section: 2)mentioning
confidence: 99%
“…It has been reported that several factors, including texture, flavor, orosensory chemical detection of fats, and postingestive effects, might contribute to food palatability. [1][2][3][4][5][6][7] Among these, the flavor of fats is considered to play an important role in increasing palatability. [8][9][10][11] Dietary fats contain many types of flavors.…”
mentioning
confidence: 99%